Borders and Frontiers of Ptolemaic and Roman Egypt. The Case of Lower Nubia - Eller, Audrey (Études et Travaux, 2025)
Drawing on Egyptian and Meroitic sources, as well as archaeological evidence from the region, this paper offers an overview and a nuanced synthesis of how the frontier was shaped in Lower Nubia during the Ptolemaic and Roman periods, spanning nearly six centuries. The interactions between Egypt, the kingdom of Meroe, and various groups of Nubian people are examined to assess the porosity of this frontier zone. Trade and religion played key roles in the development of Lower Nubia and in the formation of a distinct regional identity. By investigating this region over a long chronological span and in its full historical complexity, the paper supports recent scholarship that has called for moving beyond modern, overly rigid interpretations of ancient frontiers and for challenging asymmetrical models that portray influence as flowing exclusively from Egypt and the Roman Empire toward the kingdom of Meroe.